A case report of ectopic breast cancer of the left upper extremity with literature review - Jia, Shu-ni; Wang, Dong; Xue, Ting-ting; Zhao, Zhe-xia (Frontiers in Oncology, 2025)
Ectopic breast cancer (EBC) is a rare type of breast cancer that originates from ectopic breast tissue. This article describes a case with left breast cancer complicated by a second primary breast cancer of the left upper extremity, and summarizes the relevant literature to review the epidemiology, clinical presentation, pathologic features, imaging tests, treatment strategies, and prognosis of EBC with the aim of providing clinicians with a comprehensive reference to improve the understanding and management of this disease.